Outbreak of Crimean-Congo hemorrhagic fever in Kyzylorda region, Kazakhstan, March–July 2022 - Gazezova, Saya; Gabdullina, Malika; Ayapova, Gulzhan; Nabirova, Dilyara; Waltenburg, Michelle; Smagul, Manar; Kasabekova, Lena; Ussenov, Umirbek; Horth, Roberta (Frontiers in Public Health, 2025)
BackgroundCrimean–Congo hemorrhagic fever (CCHF) is a tick-borne zoonotic disease characterized by a high case fatality rate of ~30%. CCHF is endemic in Kyzylorda Oblast, Kazakhstan, which has a population of 800,000, with approximately 10 cases reported annually. In 2022, by end of July, 15 cases had been reported. We conducted an investigation to identify the risk factors associated with CCHF and to recommend preventive measures.MethodsWe conducted a case–control study. Case-patients were defined as individuals hospitalized between April and July 2022, showing signs consistent with CCHF and having a history of exposure—contact with ticks or animals and sudden onset of unexplained bleeding—within 2 weeks before the onset of illness. Confirmed case-patients additionally tested positive for CCHF-using both polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) for both immunoglobulin M (IgM) and immunoglobulin G (IgG) tests. For every case-patient, two people from neighboring households were selected as controls. We used logistic regression to assess the factors associated with CCHF. Ticks collected from animals residing on the case-patient’s property were tested for CCHF. We also reviewed public environmental and livestock data.ResultsWe studied 17 suspected, 7 probable, and 14 confirmed case-patients, along with 71 controls. Case-patients were predominantly male (74%), 47% were livestock workers and 37% were agricultural workers. Among the 14 confirmed CCHF case patients, 4 died from the illness (case fatality rate: 29%). Among the all case-patients, 100% reported weakness, 97% headaches, and 84% fevers. Over half (53%) of case-patients reported ticks on their bodies and clothing ≤2 weeks before the onset of the illness compared to 1% of controls (p < 0.001). Nearly half (47%) of the case-patients visited or lived in a high-risk area for tick bites ≤2 weeks before the onset of the illness compared to 6% of controls (p < 0.001). Livestock and agricultural workers had higher odds of CCHF compared to those not in these professions (odds ratios and 95% confidence interval [CI]: 3.0 [1.3–7.2] and 4.0 [1.5–10.5], respectively). Among the 55 control persons tested for CCHF, 1 (2%) tested IgG-positive. Of 163 ticks tested, 0.6% were PCR positive. In 2022, Kyzylorda had increased livestock numbers, above-average temperatures in February and March, and a delayed acaricidal treatment for livestock and pastures.ConclusionWe found a high occupational risk for CCHF. The prevalence of CCHF in ticks in our study was 0.6%, which is consistent with regional tick surveillance data. Increased tick control measures and personal protective measures for people with occupational exposure to ticks may help reduce cases.